Development and Validation of the Parent-Initiated Motivational Climate in Individual Sport Competition Questionnaire - Harwood, Chris G.; Caglar, Emine; Thrower, Sam N.; Smith, Jonathan M. J. (Frontiers in Psychology, 2019)
This paper presents a series of studies that progress the development and validation of the Parent-Initiated Motivational Climate in Individual Sport Competition Questionnaire (MCISCQ-Parent). Study 1 examined the face and content validity of an initial pool of 26 items based on the principles of achievement goal theory and prior research. In study 2, data from an adolescent sample of individual sport athletes was subjected to an exploratory factor analysis (EFA) of items pertaining to the perceived task and ego involving characteristics of fathers and mothers in the competition setting. Study 3 tested the factor structure of the MCISCQ-Parent through confirmatory factor analysis (CFA) in a further youth athlete sample. Following appropriate CFA-related modifications, good goodness of fit indices emerged for the father- (three factor-model) and mother-related (two factor model) dimensions of motivational climate. In Study 4, a further CFA was conducted and provided additional evidence for the revised factor structure of the MCISCQ-Parent, convergent and discriminant validity, and internal consistency. Finally, Study 5 provided support for the concurrent validity of the MCISCQ-Parent by demonstrating significant relationships between MCISCQ-Parent subscales and task and ego orientation, athlete engagement, and perceived social support. In sum, we present the MCISCQ-Parent as a measure with promising psychometric properties, and specifically to those applied researchers interested in assessing the quality of motivation-related parental involvement perceived by young athletes in the competition setting.